Multidisciplinary approach for crown-root fracture treatment after trauma: case report - Andriolo, Gisele Cristina Galdeano [UNESP]; Pedrini, Denise [UNESP]; Hamanaka, Elizane Ferreira [UNESP]; Luvizuto, Eloá Rodrigues [UNESP]; Barioni, Sônia Regina Panzarini [UNESP]; Sonoda, Celso Koogi [UNESP] (Editora Cubo, 2013)
The development of an accurate diagnosis and appropriate treatment plan can be a complex task, especially in cases of dentoalveolar trauma. The authors present a case report of crown-root fracture caused by trauma and highlight the importance of a multidisciplinary approach for the treatment. An eighteen year-old boy had a bicycle accident resulting in dental trauma. The upper right first molar showed a complicated crownroot fracture and the lower left second pre-molar showed an uncomplicated crown-root fracture. Endodontic treatment, controlled tooth extrusion, periodontal surgery for recovery of biological width, and porcelain crown and onlay restorations were performed. Esthetic and functional results were achieved. At the two-year follow-up it was observed that the tooth/onlay interface of the upper right first molar was stained and the onlay of the left lower second pre-molar was fractured. Therefore, the interface stained was repaired and a porcelain crown was made for the lower second premolar. The clinical case presented herein leads to the conclusion that a multidisciplinary treatment plan is extremely important for a proper resolution in cases of dentoalveolar trauma.

A elaboração de um diagnóstico preciso e de um plano de tratamento adequado pode constituir uma tarefa bastante complexa, especialmente nos casos de traumatismos dentoalveolares. O relato de caso teve por finalidade demonstrar a importância da abordagem multidisciplinar para o tratamento de fratura corono-radicular pós-traumatismo. Paciente de 18 anos de idade, gênero masculino, sofreu uma queda de bicicleta resultando em traumatismos dentários. O 16 sofreu fratura corono-radicular complicada e o 35 fratura corono-radicular não-complicada. Foi realizado tratamento endodôntico, extrusão dentária controlada, cirurgia periodontal para recuperação do espaço biológico, coroa de porcelana e restauração tipo onlay. O resultado estético e funcional foi alcançado. O paciente foi acompanhado por 2 anos onde foi observado um manchamento na interface dente/onlay do 16 e fratura da onlay do 35. Foi realizado um reparo na interface do 16 e confeccionada uma coroa de porcelana para o 35. Foi possível concluir que a multidisciplinaridade do plano de tratamento é de extrema importância para uma adequada resolução dos casos de traumatismos dentoalveolares.
Abordagem multidisciplinar para tratamento de fratura corono-radicular pós-traumatismo: relato de caso
Keywords: Crown-root fracture; Permanent tooth; Tooth injuries; Fratura corono-radicular; Dentes permanentes; Traumatismos dentários